5th AIAA Atmospheric and Space Environments Conference 2013
DOI: 10.2514/6.2013-2677
|View full text |Cite
|
Sign up to set email alerts
|

Altitude Scaling of Ice Crystal Accretion

Abstract: This paper describes experiments performed in an altitude chamber at the National ResearchCouncil of Canada (NRC) as the first step towards developing altitude scaling laws and procedures that will possibly allow aero-engines to be certified for operation in ice crystal clouds at high altitude by testing in sea level facilities. The principal objective was to test the hypothesis that accretion within a compressor due to ice crystal ingestion occurs when the local ratio of freestream liquid water content (LWC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 10 publications
5
63
0
Order By: Relevance
“…This conclusion has been based on the observation that adding ice crystals to a free stream with a wet bulb temperature below freezing led to an increase of ice growth on the leading edge, but to a decrease of ice growth further downstream. Currie et al [24,25] have also observed that at constant LWC i c /TWC ratio, the initial ice growth rate as well as the steady-state ice accretion increase proportionally with increasing TWC. At the steady-state the impinging mass flux is equal to the mass flux lost due to particle bouncing or re-impingement, phase change and erosion.…”
Section: Erosionmentioning
confidence: 94%
See 4 more Smart Citations
“…This conclusion has been based on the observation that adding ice crystals to a free stream with a wet bulb temperature below freezing led to an increase of ice growth on the leading edge, but to a decrease of ice growth further downstream. Currie et al [24,25] have also observed that at constant LWC i c /TWC ratio, the initial ice growth rate as well as the steady-state ice accretion increase proportionally with increasing TWC. At the steady-state the impinging mass flux is equal to the mass flux lost due to particle bouncing or re-impingement, phase change and erosion.…”
Section: Erosionmentioning
confidence: 94%
“…• erosion scales with the square of the tangential velocity [23,24,25], • erosion decreases for increasing IWC due to flux interference [24,25], • erosion increases for increasing melting ratio η i c = LWC i c /TWC [24,25], • erosion increases with increasing ice crystal diameter d i c [71,72], • erosion increases with increasing curvature of the surface of the ice layer [132].…”
Section: Erosionmentioning
confidence: 99%
See 3 more Smart Citations